Interferon–microRNA signalling drives liver precancerous lesion formation and hepatocarcinogenesis. Issue 7 (9th February 2016) - Yang, Yingcheng; Lin, Ximeng; Lu, Xinyuan; Luo, Guijuan; Zeng, Tao; Tang, Jing; Jiang, Feng; Li, Liang; Cui, Xiuliang; Huang, Wentao; Hou, Guojun; Chen, Xin; et al.
Abstract : Objective: Precancerous lesion, a well-established histopathologically premalignant tissue with the highest risk for tumourigenesis, develops preferentially from activation of DNA damage checkpoint and persistent inflammation. However, little is known about the mechanisms by which precancerous lesions are initiated and their physiological significance. Design: Laser capture microdissection was used to acquire matched normal liver, precancerous lesion and tumour tissues. miR-484 −/−, Ifnar1 −/− and Tgfbr2 △hep mice were employed to determine the critical role of the interferon (IFN)–microRNA pathway in precancerous lesion formation and tumourigenesis. RNA immunoprecipitation (RIP), pull-down and chromatin immunoprecipitation (ChIP) assays were applied to explore the underlying mechanisms. Results: miR-484 is highly expressed in over 88% liver samples clinically. DEN-induced precancerous lesions and hepatocellular carcinoma were dramatically impaired in miR-484 −/− mice. Mechanistically, ectopic expression of miR-484 initiates tumourigenesis and cell malignant transformation through synergistic activation of the transforming growth factor-β/Gli and nuclear factor-κB/type I IFN pathways . Specific acetylation of H3K27 is indispensable for basal IFN-induced continuous transcription of miR-484 and cell transformation. Convincingly, formation of precancerous lesions were significantly attenuated in both Tgfbr2 △hep and Ifnar1 −/− mice. Conclusions: These findings demonstrate a new protumourigenic axis involving type I IFN–microRNA signalling, providing a potential therapeutic strategy to manipulate or reverse liver precancerous lesions and tumourigenesis.